REPRESENTATION OF FEMALES IN “MULAN” BY DISNEY - Raisa Amanda Putri; Clara Kalyana Ayusya; Irma Rasita Gloria Barus (Pusat Riset dan Inovasi Nasional, 2022)
One of the most memorable films from our childhood would be